A Novel Light-Weight Subjective Trust Inference Framework in MANETs - Xia, Hui; Li, Zhetao; Zheng, Yuhui; Liu, Anfeng; Choi, Young June; Sekiya, Hiroo (IEEE Transactions on Sustainable Computing, 2020)
There is an inherent reliance on collaboration among the participants of mobile ad hoc networks in order to achieve the fixed functionalities. However, they are susceptible to the destruction of the malicious attacks or denial of cooperation. Therefore, it becomes obvious that the security issue is urgently needed to be addressed. Over the last few years, many trust-considered countermeasures have been proposed. The design of trust quantification methods is the key of these countermeasures. In this study, we abstract a novel light-weight subjective trust inference framework, which is divided into trust assessment and trust prediction. The process of node trust assessment is based on node's historical behaviours. Then utilizing the obtained trust data sequence, we introduce the SCGM(1,1)-weighted Markov stochastic chain measure to predict node's trust for future decision making. Experimental results have been conducted to evaluate the effectiveness of the proposed trust model. As an important security application, based on the standard On-Demand Multicast Routing Protocol (ODMRP), we make four major improvements which take the issue of trust into consideration, and propose a novel trust-based routing protocol called the On-Demand Trust-Based Multicast Routing protocol (ODTMRP). And finally, convincing experimental results are presented using three routing evaluation metrics.
Keywords: Computational model; Evaluation metrics; Malicious attack; Routing; Security; Trust frameworks; malicious attack; Mobile ad hoc network; routing evaluation metric; trust framework; trust-based routing protocol